Specialized active leprosy search strategies in an endemic area of the Brazilian Amazon identifies a hypermutated Mycobacterium leprae strain causing primary drug resistance - Raquel Carvalho Bouth; Angélica Rita Gobbo; Josafá Gonçalves Barreto; Josafá Gonçalves Barreto; Pablo Diego do Carmo Pinto; Maraya Semblano Bittencourt; Marco Andrey Cipriani Frade; Apolônio Carvalho Nascimento; Sabrina Sampaio Bandeira; Patricia Fagundes da Costa; Guilherme Augusto Barros Conde; Charlotte Avanzi; et al. (Frontiers in Medicine, 2023)
IntroductionLeprosy, an infectious disease caused by Mycobacterium leprae, remains a public health concern in endemic countries, particularly in Brazil. In this study, we conducted an active surveillance campaign in the hyperendemic city of Castanhal in the northeastern part of the state of Pará using clinical signs and symptoms combined with serological and molecular tools to diagnose new cases and to identify drug resistance of circulating M. leprae strains and their distribution in the community.MethodsDuring an active surveillance of one week, we enrolled 318 individuals using three different strategies to enroll subjects for this study: (i) an active survey of previously treated cases from 2006 to 2016 found in the Brazil National Notifiable Disease Information System database (n = 23) and their healthy household contacts (HHC) (n = 57); (ii) an active survey of school children (SC) from two primary public schools in low-income neighborhoods (n = 178), followed by visits to the houses of these newly diagnosed SC (n = 7) to examine their HHC (n = 34) where we diagnosed additional new cases (n = 6); (iii) and those people who spontaneously presented themselves to our team or the local health center with clinical signs and/or symptoms of leprosy (n = 6) with subsequent follow-up of their HHC when the case was confirmed (n = 20) where we diagnosed two additional cases (n = 2). Individuals received a dermato-neurological examination, 5 ml of peripheral blood was collected to assess the anti-PGL-I titer by ELISA and intradermal earlobe skin scrapings were taken from HHC and cases for amplification of the M. leprae RLEP region by qPCR.ResultsAnti-PGL-I positivity was highest in the new leprosy case group (52%) followed by the treated group (40.9%), HHC (40%) and lowest in SC (24.6%). RLEP qPCR from SSS was performed on 124 individuals, 22 in treated cases, 24 in newly diagnosed leprosy cases, and 78 in HHC. We detected 29.0% (36/124) positivity overall in this sample set. The positivity in treated cases was 31.8% (7/22), while in newly diagnosed leprosy cases the number of positives were higher, 45.8% (11/23) and lower in HHC at 23.7% (18/76). Whole genome sequencing of M. leprae from biopsies of three infected individuals from one extended family revealed a hypermutated M. leprae strain in an unusual case of primary drug resistance while the other two strains were drug sensitive.DiscussionThis study represents the extent of leprosy in an active surveillance campaign during a single week in the city of Castanhal, a city that we have previously surveyed several times during the past ten years. Our results indicate the continuing high transmission of leprosy that includes fairly high rates of new cases detected in children indicating recent spread by multiple foci of infection in the community. An unusual case of a hypermutated M. leprae strain in a case of primary drug resistance was discovered. It also revealed a high hidden prevalence of overt disease and subclinical infection that remains a challenge for correct clinical diagnosis by signs and symptoms that may be aided using adjunct laboratory tests, such as RLEP qPCR and anti-PGL-I serology.